A quantum approach to calculate differential and total cross sections for electron impact ionization of molecular targets. Issue 15 (January 2020) - Mouawad, L; Hervieux, P-A; Dal Cappello, C; Pansanel, J; Robert, V; El Bitar, Z
Synopsis: We present a theoretical approach to calculate the cross sections for the ionization of molecules by single electron impact. It is based on the First Born approximation (FBA), describing the ejected electron by a distorted wave (DW). The cross sections are calculated for an average molecular orientation with the proper average method. Single-center molecular wave functions are generated using Gaussian making this method easily applicable to any molecule. We show the calculated cross sections of some molecular targets of varying complexity.